2018
DOI: 10.1080/03075079.2018.1493097
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of success: first-year student success in multiple domains

Abstract: The goal of this study was to examine differences in university success between first-year students by analyzing three domains simultaneously: students' academic achievement, critical thinking disposition, and socialemotional adjustment to university life. Participants were 307 students who completed an online questionnaire. Latent class cluster analysis revealed three patterns of success: (1) average-achieving well-adjusted students (64%), (2) high-achieving average-adjusted students (14%), and (3) low-achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…This implied that some students who suddenly experienced fully online education superficially adapted to the new school environment while exhibiting many mental health problems. The present results differ from a previous study that found three patterns of school success in a period with the usual education system: well-adjusted average academic achiever; average-adjusted high achiever, and low-adjusted low achiever ( 18 ), although it is difficult to compare the findings directly owing to methodological differences. Difficulty in maintaining motivation could explain the characteristics of school adaptation in students exposed to online education.…”
Section: Discussioncontrasting
confidence: 99%
“…This implied that some students who suddenly experienced fully online education superficially adapted to the new school environment while exhibiting many mental health problems. The present results differ from a previous study that found three patterns of school success in a period with the usual education system: well-adjusted average academic achiever; average-adjusted high achiever, and low-adjusted low achiever ( 18 ), although it is difficult to compare the findings directly owing to methodological differences. Difficulty in maintaining motivation could explain the characteristics of school adaptation in students exposed to online education.…”
Section: Discussioncontrasting
confidence: 99%
“…As for academic factors, variables that were found to be associated with students' academic adjustment were learning engagement and goal orientations (Wang et al, 2021 ), intention to drop out and academic self-efficacy (Girelli et al, 2018 ), and high school GPA and obtained credit points (van der Zanden et al, 2019 ). Considering individual factors, several other variables were found to be associated with students' academic adjustment.…”
Section: Resultsmentioning
confidence: 99%
“…For each question, respondents were also given the response option "prefer not to say." Previous research has shown that students' self-reported GPAs are highly correlated with their GPAs as they appear in university records (van der Zanden et al, 2018), and students at the institution where this study took place can always view their GPA for each year of study in the institution's online student information system. Thus, students' self-report of current and first year GPA should be a reasonable proxy for academic achievement during those time periods.…”
Section: Academic Achievementmentioning
confidence: 99%